Recent Progress on NiFe‐Based Electrocatalysts for the Oxygen Evolution Reaction - Zhao, Jia; Zhang, Ji‐Jie; Li, Zhao‐Yang; Bu, Xian‐He (Small (Weinheim an der Bergstrasse, Germany), 2020)
The seriousness of the energy crisis and the environmental impact of global anthropogenic activities have led to an urgent need to develop efficient and green fuels. Hydrogen, as a promising alternative resource that is produced in an environmentally friendly and sustainable manner by a water splitting reaction, has attracted extensive attention in recent years. However, the large‐scale application of water splitting devices is hindered predominantly by the sluggish oxygen evolution reaction (OER) at the anode. Therefore, the design and exploration of high‐performing OER electrocatalysts is a critical objective. Considering their low prices, abundant reserves, and intrinsic activities, NiFe‐based bimetal compounds are widely studied as excellent OER electrocatalysts. Moreover, recent progress on NiFe‐based OER electrocatalysts in alkaline environments is comprehensively and systematically introduced through various catalyst families including NiFe‐layered hydroxides, metal–organic frameworks, NiFe‐based (oxy)hydroxides, NiFe‐based oxides, NiFe alloys, and NiFe‐based nonoxides. This review briefly introduces the advanced NiFe‐based OER materials and their corresponding reaction mechanisms. Finally, the challenges inherent to and possible strategies for producing extraordinary NiFe‐based electrocatalysts are discussed. This review briefly introduces the advanced NiFe‐based oxygen evolution reaction (OER) materials and their corresponding reaction mechanisms. After providing this background, recent progress on NiFe‐based OER electrocatalysts through various catalyst families is comprehensively and systematically presented, and the inherent challenges and probable strategies for producing extraordinary NiFe‐based electrocatalysts are finally discussed.